2019
DOI: 10.21203/rs.2.11898/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can ELABELA be a Novel Target in the Treatment of Chronic Lymphocytic Leukaemia?

Abstract: Background: It has been shown that bcl2, bcl-XL and mcl-1 protein levels are high in chronic lymphocytic leukemia cells, and resultantly, apoptosis does not occur chronic lymphocytic leukemia cells. Apelin and apela (ELABELA/ELA/Toddler) are two peptide ligands for a class A G-protein coupled receptor called apelin receptor. Studies have shown that ELA inhibits apoptosis by inhibiting apoptotic proteins and activating anti-apoptotic proteins. Proteins and genes involved in apoptosis are valuable for targeted … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chronic lymphocytic leukemia (Acik et al 2019) Elevated Apela (endogenous APJ agonist) may may potentiate progress of chronic lymphocytic leukemia.…”
Section: Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic lymphocytic leukemia (Acik et al 2019) Elevated Apela (endogenous APJ agonist) may may potentiate progress of chronic lymphocytic leukemia.…”
Section: Bloodmentioning
confidence: 99%
“…It was recently demonstrated that blood levels of Apela (together with Apelin, endogenous agonist for the APJ receptor), were elevated in individuals with chronic lymphocytic leukemia (CLL) (Acik et al 2019). Accordingly, it was anticipated that a similar situation may occur in acute myeloid leukemia (after APJ overexpression), and a thorough screening of AML cell lines was carried out (Figure 3).…”
Section: Expression and Regulation Of Apelin And Apj Expressionmentioning
confidence: 99%